Order optimal real-time observers for completely observable control systems - Kryazhimskii, Arkadii (Zielona Góra: Uniwersytet Zielonogórski)
For a complety observable control system governed by a nonlinear ordinary differential equation, we consider dynamical (real-time) observation operators stable with respect to small input perturbations. We treat them as regularizing operators on an appropriate set of well-posedness. Two solutions order optimal with respect to the perturbation accuracy are described. The tool is based on the idea of guided models from the theory of closed-loop differential games, and the lower bounds for the unimprovable observation accuracy.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka